2020
DOI: 10.2147/jaa.s245161
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical Features and Disease Course of Primary Angioedema Patients in a Tertiary Care Hospital</p>

Abstract: Purpose: To give a better understanding of primary AE, the clinical characteristics and the possible therapeutic approaches. Background: Angioedema (AE) is a non-pitting, non-itching swelling of skin or mucosa. The symptom can become life-threatening if located in the airways. Primary (monosymptomatic) AE is a manifestation of several different diseases and the diagnosis is not always straightforward. The aetiological and pathophysiological factors of primary AE are not completely clarified. There is a need fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…In preceding studies, the effect of antihistamines in AE patients was analysed with regard to the current classification of AAE, which defines patients as IH‐AAE or InH‐AAE based on the response to antihistamine therapy 2,3 . The effect of antihistamines on AE was previously studied mainly in AE patients without wheals 10–13 . These studies found similar complete response rates at follow‐up after antihistamine monotherapy (in variable dosage) ranging from 56% to 72% 10,11 and improvement of attack frequency in 86%–91% 12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…In preceding studies, the effect of antihistamines in AE patients was analysed with regard to the current classification of AAE, which defines patients as IH‐AAE or InH‐AAE based on the response to antihistamine therapy 2,3 . The effect of antihistamines on AE was previously studied mainly in AE patients without wheals 10–13 . These studies found similar complete response rates at follow‐up after antihistamine monotherapy (in variable dosage) ranging from 56% to 72% 10,11 and improvement of attack frequency in 86%–91% 12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Histamine-mediated angioedema is caused by the same underlying pathologic mechanism as wheals but occurs deeper in the skin. Angioedema is a common reason for ED visits [ 21 ] and can be life-threatening if the airway is involved [ 22 , 23 ]. H 1 antihistamines, along with corticosteroids, are first-line treatment for histamine-mediated angioedema without anaphylaxis [ 23 ].…”
Section: Treatment Of Angioedemamentioning
confidence: 99%
“…It is self-limited, often asymmetrical, and can be life threatening if associated with airway compromise and/or anaphylaxis. While hereditary AE has been examined thoroughly in the literature, [1][2][3] there is much to be discovered of the acquired and idiopathic forms. This case reports a new onset unspecified postoperative angioedema, possible etiologies, and best treatment practices.…”
Section: Introductionmentioning
confidence: 99%